DNA damage response in neurodevelopment and neuromaintenance - Qing, Xiaobing; Zhang, Guangyu; Wang, Zhao‐Qi (The FEBS journal, 2023)
The central nervous system is particularly susceptible to DNA repair deficiency, which renders a variety of neurodevelopmental and neurodegenerative disorders in humans. It is generally believed that DNA damage occurs upon repetitive replication and oxidative stress in highly proliferating neuroprogenitor cells (NPs), or due to high rates of metabolism and active neuronal activity in terminally differentiated neurons. DNA double‐stranded breaks (DSBs) and single‐stranded breaks (SSBs) constitute the most prevalent forms of DNA damage, which can result in neuronal apoptosis if unrepaired. Despite these notions, there are still gaps in our knowledge regarding the mechanism and specificity of DNA damage and repair in the neural development and the homeostasis of neural tissues. Recent studies have identified recurrent DSBs within neuronal long genes in NPs and ‘programmed’ SSBs in neuronal activity genes. However, the physiological function of these DNA breakages in the nervous system has not been so far explored. In this review, we summarise the recent advances in the field of DNA damage and DNA repair in neural development and neuropathies. Programmed DNA breaks occur in neural progenitors during gene rearrangement. In neuronal cells, intrinsic and extrinsic signals can induce DNA breaks in promoters of response genes. Under DNA repair deficient conditions, these DNA damages accumulate and represent an etiological factor for human neurodevelopmental and neurodegenerative pathologies. Here, we summarise recent research on ‘programmed’ DNA breaks and their repair in these neural cells and imply their physiological functions in the nervous system.